2005
DOI: 10.1080/00365540510031700
|View full text |Cite
|
Sign up to set email alerts
|

Demographics in HIV-infected children in Denmark: Results from the Danish Paediatric HIV Cohort Study

Abstract: We present the demographic data on HIV-infected children from the Danish Paediatric HIV Cohort Study, an observational database on HIV in Denmark. Up to 1 July 2003 a total of 89 children had been diagnosed with HIV infection before the age of 16 y, of which 12 (13.5%) had died, 2 (2.2%) had emigrated from Denmark, and 13 had reached the age of 16 y. Estimates of prevalence and incidence of HIV infection in the area were 5.77/100,000 and 0.39/100,000 respectively, which are lower than in the adult population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…[3][4][5][6]28,29 Also consistent with this study, earlier reports on HIV-infected children have shown that children born in SSA were older at HIV diagnosis and at cART initiation as compared with children born in the described industrialized country. 2,3,21 After excluding children with no registered clinical conditions, the maximum CDC clinical category was not different between children born in NL and SSA. This is in contrast with adult studies, where immigrants generally showed a poorer clinical state than native patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[3][4][5][6]28,29 Also consistent with this study, earlier reports on HIV-infected children have shown that children born in SSA were older at HIV diagnosis and at cART initiation as compared with children born in the described industrialized country. 2,3,21 After excluding children with no registered clinical conditions, the maximum CDC clinical category was not different between children born in NL and SSA. This is in contrast with adult studies, where immigrants generally showed a poorer clinical state than native patients.…”
Section: Discussionsupporting
confidence: 93%
“…1 Since then, most new HIV-infected children in NL were immigrants and adopted children from sub-Saharan Africa (SSA), as also reported in several other industrialized countries. [2][3][4][5][6] In the adult population, essential differences in characteristics and outcomes between HIV-infected immigrants and nonimmigrants residing in industrialized countries have been described. In the Swiss cohort, HIV-infected immigrants from SSA were younger, predominantly female, and more frequently infected through heterosexual activity as compared with nonimmigrants.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is largely applied to migrants from SSA in Europe (Denmark, 37 France, 38 Spain 18 , 23 and UK 25 , 32 , 34 ) and Canada 9 , 30 , 31 . Other studies consider some migrants may have acquired HIV in countries of destination because of unfavourable environment to fostering preventive behaviours 11 , 39 , 40 .…”
Section: Resultsmentioning
confidence: 99%
“…Some countries have taken targeted approaches to HIV testing in antenatal care. For example, Denmark switched from routine to HIV selective antenatal screening in 1995; HIV testing was only offered to women from high prevalence countries since almost all HIV-positive pregnant women identified were migrants or married to migrants from high prevalence countries 37 . However, a few HIV-positive babies were born subsequently, resulting in the reintroduction of universal screening.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, most HIV infections in migrants in Europe, particularly among those from Sub-Saharan African (SSA), were assumed to have been imported [8,9]. There is mounting evidence that HIV infections in migrants are being increasingly acquired postmigration [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%